Prevalence studies of vancomycin-resistant enterococci for monitoring a passive surveillance program in a pediatric hospital - Lopardo, Horacio (2006)
Fil: Lopardo, H. Hospital de Pediatría Prof. Dr. Juan P. Garrahan, Buenos Aires; Argentina